A Interfaith Marriage based on Positive Law and Protestantism Perspective - Herry Anto Simajuntak (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
Interfaith marriage is currently being widely discussed and is actually not a new thing for the multicultural Indonesian people. The marriage has occurred in the community (in various social dimensions) and has been going on for a long time. However, it does not also mean that the issue of interfaith marriage is not a problem, in fact it tends to always reap controversy among the public. There is an assumption that the cause is the existence of Law no. 1 of 1974 as amended by Law no. 16 of 2019 concerning Marriage, which does not accommodate interfaith marriage issues. The problems that have arisen recently are interfaith marriages are also widely opposed among the community, for example among Protestant Christians, because interfaith marriages are still considered taboo because according to Protestant Christianity, interfaith marriages will cause new problems in the future for descendants and in administration. Therefore, until now, there is no Protestant Christian religious leader who has agreed to legalize interfaith marriages because it is written in the Bible 2 Corinthians 6:14, which reads: